The Perceptions Of Malaysian Undergraduate Students About A Set Of Generic Skills - Abdullah Sani, Kamaluddin (2007)
This article reports the perceptions of Malaysian undergraduate students toward a set of generic skills using a factor analysing approach and explores the relationships between factors. A Generic Skills Survey was employed as the basis of this investigation and distributed to undergraduate students from three public universities in Peninsular Malaysia. A factor analysis of 460 responses identified five dominant skills in a set of generic skills. Correlation tests indicated that all skills were significantly correlated. It was concluded that the five skills became an integrated entity of the set of generic skills perceived by Malaysian undergraduate students. Statistical evidences in exploring the generic skills were presented and some implications in the context of Malaysian were discussed.